Chemical activation of a food deprivation signal extends lifespan - Lucanic, Mark; Garrett, Theo; Yu, Ivan; Calahorro, Fernando; Asadi Shahmirzadi, Azar; Miller, Aaron; Gill, Matthew S.; Hughes, Robert E.; Holden‐Dye, Lindy; Lithgow, Gordon J. (Aging cell, 2016)
Summary Model organisms subject to dietary restriction (DR) generally live longer. Accompanying this lifespan extension are improvements in overall health, based on multiple metrics. This indicates that pharmacological treatments that mimic the effects of DR could improve health in humans. To find new chemical structures that extend lifespan, we screened 30 000 synthetic, diverse drug‐like chemicals in Caenorhabditis elegans and identified several structurally related compounds that acted through DR mechanisms. The most potent of these NP1 impinges upon a food perception pathway by promoting glutamate signaling in the pharynx. This results in the overriding of a GPCR pathway involved in the perception of food and which normally acts to decrease glutamate signals. Our results describe the activation of a dietary restriction response through the pharmacological masking of a novel sensory pathway that signals the presence of food. This suggests that primary sensory pathways may represent novel targets for human pharmacology.